Search for top quark FCNC couplings in Z′ models at the LHC and CLIC - Cakir, O.; Cakir, I. T.; Senol, A.; Tasci, A. T. (Springer Science and Business Media LLC, 2010)
The top quark is the heaviest particle to date discovered, with a mass close to the electroweak symmetry breaking scale. It is expected that the top quark would be sensitive to the new physics at the TeV scale. One of the most important aspects of the top quark physics can be the investigation of the possible anomalous couplings. Here, we study the top quark flavor changing neutral current (FCNC) couplings via the extra gauge boson Z' at the Large Hadron Collider (LHC) and the Compact Linear Collider (CLIC) energies. We calculate the total cross sections for the signal and the corresponding Standard Model (SM) background processes. For an FCNC mixing parameter x=0.2 and the sequential Z' mass of 1 TeV, we find the single top quark FCNC production cross sections 0.38(1.76) fb at the LHC with sqrt{s_{pp}}=7(14) TeV, respectively. For the resonance production of sequential Z' boson and decays to single top quark at the Compact Linear Collider (CLIC) energies, including the initial state radiation and beamstrahlung effects, we find the cross section 27.96(0.91) fb at sqrt{s_{e^{+}e^{-}}}=1(3) TeV, respectively. We make the analysis to investigate the parameter space (mixing-mass) through various Z' models. It is shown that the results benefit from the flavor tagging.

20 pages, 17 figures, 6 tables
Keywords: High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); FOS: Physical sciences; 7. Clean energy